HLA-DRB1∗1502 Is Associated With Anti-N-Methyl-D-aspartate Receptor Encephalitis in Thai Children - Anurat K. (2023)
Background: Anti-N-methyl-D-aspartate receptor encephalitis (anti-NMDARE) is one of the most common types of autoimmune encephalitis. Most patients have no apparent immunologic triggers, which suggests a genetic predisposition. This study was conducted to identify human leukocyte antigen (HLA) class II alleles associated with anti-NMDARE in Thai children. Methods: This case-control study enrolled patients younger than 18 years who were diagnosed with anti-NMDARE between January 2010 and December 2020. A “good outcome” was determined as a patient with a modified Rankin scale score of less than 2 at any follow-up visit. HLA genotypes were determined at four-digit alleles using reverse sequence-specific oligonucleotide probe hybridization. The HLA class II allele frequency in patients was compared with that in a database of 101 healthy control Thai children. Results: Thirty-four patients were enrolled with a mean age of 12.8 ± 5.6 years (females 85.3%). The HLA-DRB1∗1502 allele frequency was significantly higher in patients than in controls (odds ratio, 2.32; 95% confidence interval, 1.11-4.8, P = 0.023). A good outcome was noted in 14 of 14 (100%) HLA-DRB1∗1502-positive patients (median time to a good outcome, 6 months) and 14 of 17 (82.3%) HLA-DRB1∗1502-negative patients (median time to a good outcome, 3 months). Two (11.8%) HLA-DRB1∗1502-positive patients had one relapse each, and six (35.3%) HLA-DRB1∗1502-negative patients had one to three relapses. Conclusions: HLA-DRB1∗1502 was significantly associated with anti-NMDARE in our patients. Most patients had good outcomes. HLA-DRB1∗1502-positive patients tended to require a longer time to achieve a good outcome but had less frequent relapses than HLA-DRB1∗1502-negative patients.